Perceived justice and consumer post service failure behaviour: the moderating role of failure severity, attachment styles, and brand authenticity - Randhir-Singh, Sarabjit Kaur (2021)
This study aims to investigate the role of failure severity, attachment styles and brand authenticity within the failure and recovery framework, which is widely recognised as fundamental in the body of research for service failure and recovery. Failure severity is a critical factor influencing consumers’ perceived justice of recovery efforts and corresponding satisfaction. However, most studies tend to address failure severity at one level even though it can be of low and high levels, which consequently impacts recovery satisfaction and behavioural responses differently. Past studies have also found mixed findings on the impact that recovery satisfaction can have on positive behavioural responses, and the extant literature indicates that personality traits and brand-related factors can better explain consumer behaviours.